Potential genetic gain in dairy production of Holstein Friesian cattle applying a selection index - Chagunda, Mizeck G.G.; Wollny, C.B.A.; Bruns, E.W. (2002)
This study was undertaken to estimate the potential genetic gains in milk yield by using several alternative selection criteria which included milk yield and reproductive traits of dairy cattle in Malawi. Applying the selection index procedure, the expected genetic gain in each trait in the different scenarios was calculated for bull performance. On average, there were six daughters per sire. Including calving interval in the selection criteria increased expected genetic gain by 55.9% for milk yield and 94.4 % for calving interval from the currently applied selection criteria after one round of selection. The correlation between the index and the aggregate genotype (rHI), which indicates the accuracy of estimation, increased from 0.221 to 0.495. Adding age at first calving in the selection criteria resulted in very minimal increases. The optimal breeding strategy for the aggregate genotype which aims at improving milk yield and calving interval, is one whose selection criteria is based on milk yield and calving interval obtained from daughters performing in Malawi.